HER2-low expression does not affect the clinical outcomes of metastatic breast cancer treated with CDK4/6 inhibitor: A real-world study - Shao, Yingbo; Luo, Zhifen; Yu, Yang; Chen, Qi; He, Yaning; Liu, Chaojun; Nie, Bing; Zhu, Fangyuan; Liu, Hui (Frontiers in Endocrinology, 2022)
Background: There is accumulating evidence support human epidermal growth factor receptor 2 (HER2)-low as a biologically distinct subtype of breast cancer. The present study was conducted to explore whether HER2-low expression will affect the clinical efficacy of cyclin-dependent kinase (CDK) 4/6 inhibitor for patients with hormone receptor (HR)-positive, HER-2 negative metastatic breast cancer. Methods: Patients with HR+/HER2- metastatic breast cancer who were treated with palbociclib from January 2019 to June 2021 were retrospectively analyzed based on real-world clinical practice. HER2-zero was defined as immunohistochemistry (IHC) 0, and HER2-low was defined as IHC 1+ or IHC 2+/fluorescence in situ hybridization (FISH) negative. The primary end point was progression free survival (PFS), and the secondary end points were objective response rate (ORR), disease control rate (DCR), overall survival(OS) and safety. Results: 45 patients received palbociclib plus aromatase inhibitor (AI) or fulvestrant therapy, including 24 HER-2-zero and 21 HER-2-low patients. There were no statistically significant differences in clinicopathological characteristics between the two groups. No significant differences were observed in ORR (41.7% vs. 28.6%, P=0.360) and DCR (79.2% vs. 76.2%, P=0.811) between HER-2-zero and HER-2-low patients. And simultaneously, HER2-zero and HER2-low patients obtained similar median PFS (16.2m vs. 14.1m, P=0.263). The median OS was not reached. Neutropenia and leukopenia were the most common adverse events. Grade 3-4 adverse events(AEs) occurred in 58.3% and 57.1% of patients, respectively. Conclusions: HER2-low expression does not affect the clinical efficacy of palbociclib and our present study did not support incorporating HER2-low into systemic therapy decisions for patients with HR+/HER2- metastatic breast cancer treated with CDK4/6 inhibitor.